Congenital pouch colon in a girl associated with bilateral atresia of cervix uteri and uterus didelphys - Rajiv Chadha; Manju Puri; Rahul Saxena; Surendrakumar Agarwala; Archana Puri; Subhasis Roy Choudhury (Wolters Kluwer Medknow Publications, 2013)
This report describes a girl with congenital pouch colon (CPC), uterus didelphys with septate vagina, and a cloacal anomaly. The girl underwent cloacal reconstruction at the age of 15 months. Subsequently, at puberty, the child had primary amenorrhea with severe cyclic abdominal pain due to endometriosis of both the uteruses and adnexal cysts with hematometra and hematosalpinx. Laparotomy with removal of both uteri and the left fallopian tube was performed. Both uteri had atresia of the cervix uteri. This report emphasizes the need for comprehensive evaluation and a long-term management strategy for associated gynecologic anomalies in girls with CPC, especially with regard to patency of the outflow tract.